2017
DOI: 10.1103/physrevapplied.7.034031
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Models for Nonreciprocal Amplification Using Biharmonic Drives

Abstract: We present a generic system of three bosonic modes coupled parametrically with a time-varying coupling modulated by a combination of two pump harmonics, and we show how this system provides the minimal platform for realizing nonreciprocal couplings that can lead to gainless photon circulation, and phase-preserving or phase-sensitive directional amplification. Explicit frequency-dependent calculations within this minimal paradigm highlight the separation of amplification and directionality bandwidths, a feature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Such directional amplification has been experimentally demonstrated in Josephson circuits [6], [11], and in optomechanical microtoroid cavities [20][21], while it has been shown that a generic system of three harmonic modes, coupled parametrically through two pump harmonics, serves as a minimal system for directional amplification [12]. In all examples discussed so far, we considered operation in the red-detuned regime, which is the most commonly considered in optomechanical systems for non-reciprocity and isolation.…”
Section: Non-reciprocal Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such directional amplification has been experimentally demonstrated in Josephson circuits [6], [11], and in optomechanical microtoroid cavities [20][21], while it has been shown that a generic system of three harmonic modes, coupled parametrically through two pump harmonics, serves as a minimal system for directional amplification [12]. In all examples discussed so far, we considered operation in the red-detuned regime, which is the most commonly considered in optomechanical systems for non-reciprocity and isolation.…”
Section: Non-reciprocal Amplificationmentioning
confidence: 99%
“…Microring resonators with a traveling wave index modulation, acting as an angular momentum bias, have been proposed as an efficient way to break reciprocity in compact devices [6]- [7], a concept that has been realized in a discretized arrangement of resonators with out-of-phase temporal modulations [8]- [9]. In addition, parametrically coupled multimode systems have been also shown to perform non-reciprocal frequency conversion and amplification [10]- [12], for example based on Josephson junctions [13]. Recently, it has been realized that optomechanical coupling can also be used to impart the required form of synthetic gauge required to induce electromagnetic non-reciprocity at optical [14]- [22] and microwave frequencies [23], [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the quantitative agreement between data and theory we show here will be crucial for further optimizing performance within experimental constraints as well as developing more complex multimode systems. While we have pursued ideal isolation, which preserves quantum signals, the parameters we demonstrate here are also well suited for implementing nonreciprocal amplification schemes [11,15,18,20,25,36].…”
mentioning
confidence: 99%
“…As a crucial element in signal readout and information processing, directional optical amplifiers (with minimal noises from the output port) have also been proposed and studied, in microwave circuits [44,45] or a non- * jinghui73@foxmail.com Hermitian time-Floquet device [46]. In a recent experiment, a reconfigurable optical device was demonstrated [47], having switchable functions as either a circulator or a directional amplifier [48,49]. Directional amplification of microwave signals has also been experimentally demonstrated in a multi-mode COM system [50].…”
Section: Introductionmentioning
confidence: 99%